Evaluation of the FNA accuracy in differentiating malignant from non-malignant thyroid nodules in comparison with postoperative histopathological findings - Erfanifar, Azam; yousefzad, Tayebe; Rashidi, Homeira; Amouzegar, Atieh; Sarmast Shushtari, Mohammad Hossein; fanaei, Seyad Ahmad; Emadmootofi, Neptune; Azizi, Fereidoun; Kalbasi, Saeed (Student Research in Translational Medicine, 2022)
Background and aim:: Thyroid nodules are one of the most common thyroid disorders and due to these nodules have a chance for malignancy, all thyroid nodules should be evaluated cytologically. The choice method for this assessment is fine needle aspiration (FNA). Different studies have reported different values for the diagnostic power of FNA compared to the pathological evaluation of the surgical specimen. In this study, we aimed to evaluate the power of FNA in comparison with postoperative histopathological findings in differentiating malignant thyroid nodules from non-malignant nodules. Materials and Methods: In this diagnostic study, the records of patients with thyroid nodules who required diagnostic FNA based on the findings of clinical examination and diagnosis (ultrasound and TSH) were evaluated. The data of 359 patients with FNA and cytopathology results were assessed based on a surgical specimen. Results: Of these 359 patients, 279 (77.7%) were women and 80 (22.3%) were men. The mean age of the patients was 43.28 ± 13.37 years. The mean age of patients in the group with benign thyroid nodules was significantly higher than patients with malignant thyroid nodules (P-value = 0.001). For FNA, sensitivity was 74%, specificity was 86%, positive predictive value was 76% and finally negative predictive value was 85%. The accuracy of FNA was 82%. Conclusion: FNA can be used in most nodules. Of course, accompanying with clinical findings should be considered.